2012
DOI: 10.1007/s00066-011-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Die Strahlensensitivität humaner Tumorzelllinien ist unabhängig von der basalen HIF-1α-Expression

Abstract: Our data suggest that basal HIF-1α levels in human tumor cell lines do not predict their radiosensitivity under normoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…1A, black bars, right graph). As demonstrated previously, the inability of H1339 cells to up-regulate HIF-1α in response to hypoxia can neither be explained by varying cell densities, absence / presence of growth factors nor by reoxygenation effects [13]. In contrast to HIF-1α, HIF-2α was up-regulated upon hypoxic exposure in both tumor cell lines (Fig.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…1A, black bars, right graph). As demonstrated previously, the inability of H1339 cells to up-regulate HIF-1α in response to hypoxia can neither be explained by varying cell densities, absence / presence of growth factors nor by reoxygenation effects [13]. In contrast to HIF-1α, HIF-2α was up-regulated upon hypoxic exposure in both tumor cell lines (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Although elevated HIF-1α levels were previously reported to be predictive for radioresistance [11] our findings show an increased radiosensitivity in tumors with high basal HIF-1α levels. This finding was confirmed in a larger panel of tumor cell lines derived from different entities [24] .…”
Section: Resultssupporting
confidence: 60%
“…In our animal study, immunohistochemical analysis clearly revealed p21 expression and apoptosis in tumor tissues within 4 days after RT rather than 14 days later, when the molecular responses may have passed, potentially indicating that the change in tumor size was a net effect of RT. Clinical trials and mechanistic studies are urgently required to identify appropriate radiosensitizers for administering RT for oral squamous cell carcinoma [4851]. Concurrent chemoradiation therapy has improved locoregional control and patient survival; however, locoregional failure remains a significant problem [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that HIF-1 plays a pivotal role in hypoxia-induced tumor radioresistance (Moeller and Dewhirst, 2006; Harada, 2011). In this context, our own investigations revealed no correlation between basal HIF-1α levels and the survival fraction in irradiated tumor cell lines implying that basal HIF-1α levels in human tumor cell lines obviously do not predict their radiosensitivity under normoxia (Schilling et al, 2012a). Moreover, HIF-1α has been found as being responsible for genetic instability to down-regulated MMR proteins by inhibiting the MMR proteins MSH-2 and MSH-6, thereby decreasing levels of the MSH-2/MSH-6 complex, MutSα, which recognizes base mismatches.…”
Section: Genetic Instabilitymentioning
confidence: 95%